Flip-Flop SR Latch Logic Operation for Spin Orbit Torque-Magnetic Tunnel Junction Circuitry - Loy, Desmond Jia Jun (2016)
In recent years, spin transfer torque (STT)-magnetic random access memory (MRAM) was seen as one of the most promising candidates for next-generation non-volatile memory. STT-MRAM was seen as a potential candidate to replace complementary metal oxide semiconductor (CMOS)-based memory in the field of logic-in-memory. However, STT-MRAM also faces challenges such as high energy consumption and weakened reliability due to a common access path for both read and write operations. This compels the search for a new spintronic concept known as spin orbit torque (SOT)-MRAM. The core of a MRAM is the magnetic tunnel junction (MTJ) cell. A SOT-MTJ is a three-terminal device which has its read and write paths isolated, and it consist of better overall properties as compared to an STT-MTJ, making SOT-MTJ a suitable novel paradigm for logic applications. In this work, we demonstrate a prototype SOT-based MTJ SR-latch circuit which has faster switching time and shorter energy delay as compared to conventional semiconductor counterparts. [2nd Award]